Business strategy for Vinh Tuong industrial corporation in competiting with the big foreigner corporations : Luận văn ThS. Kinh doanh và quản lý: 60 34 05 - Nguyễn, Thị Mai Lan (Đại học Quốc gia Hà Nội, 2017)
Electronic Resources